2009
DOI: 10.4049/jimmunol.0803226
|View full text |Cite
|
Sign up to set email alerts
|

NontypeableHaemophilus influenzaeProtein E Binds Vitronectin and Is Important for Serum Resistance

Abstract: Nontypeable Haemophilus influenzae (NTHi) commonly causes local disease in the upper and lower respiratory tract and has recently been shown to interfere with both the classical and alternative pathways of complement activation. The terminal pathway of the complement system is regulated by vitronectin that is a component of both plasma and the extracellular matrix. In this study, we identify protein E (PE; 16 kDa), which is a recently characterized ubiquitous outer membrane protein, as a vitronectin-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 82 publications
(148 citation statements)
references
References 44 publications
6
140
0
2
Order By: Relevance
“…E. coli harboring pET26bhpe or pET16bhpe (Hallstrom et al, 2009;Singh et al, 2013) were grown in LB broth in the presence of 50 µg/ml kanamycin or 100 µg/ml ampicillin, respectively.…”
Section: Bacterial Strains and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli harboring pET26bhpe or pET16bhpe (Hallstrom et al, 2009;Singh et al, 2013) were grown in LB broth in the presence of 50 µg/ml kanamycin or 100 µg/ml ampicillin, respectively.…”
Section: Bacterial Strains and Reagentsmentioning
confidence: 99%
“…PE was initially described as an adhesin that binds to epithelial cells of different origins including those from COPD patients (Ronander et al, 2009). In addition, PE simultaneously binds to extracellular matrix proteins and plasminogen, interactions that all contribute to bacterial virulence (Barthel et al, 2012;Hallstrom et al, 2009;Hallstrom et al, 2011). We recently crystallized PE and showed that it is a dimer with multiple binding sites for proteins derived from the host (Hallstrom et al, 2011;Singh et al, 2012;Singh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…NTHi has recently been reported to bind to ECM-proteins such as Ln and vitronectin [17,18,29]. Here, we report the NTHi ABC-transporter protein PF to be a novel Lnand cell-binding adhesin.…”
Section: Discussionmentioning
confidence: 81%
“…Bacteria loaded with FH are, however, still exposed to the other pathways of the complement system. Hence, to avoid serum killing from all pathways, H. influenzae also recruits the complement regulator C4b-binding protein, the major soluble regulator of the classical and the lectin pathway, in addition to vitronectin, which inhibits the formation of the lytic MAC (20,22,23,63). Another strategy to circumvent the deleterious effects of complement relies on masking the structures which interact with activators of complement.…”
Section: Discussionmentioning
confidence: 99%
“…H. influenzae has been shown to escape serum-mediated killing by binding FH and C4b-binding protein, the latter governs the classical pathway of complement activation, but also vitronectin, which results in inhibition of the terminal pathway and formation of the MAC (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%